Sounding out a record of Gospel effort at home and abroard by Australian assemblies - Saxby, Maurice Henry, 1900-1988 (Chatswood, NSW Australian Missionary Tidings, 1973)
Includes index and photographs.
Keywords: Missions -- brethren movement -- Australian origins